Detection of pathogenic Leptospira in rats and phylogenetic analysis using outer membrane lipoprotein Lipl32 gene at two major public markets - Wan, Steffi Julan; Sulaiman, Nurshahira; Zulkifli, Nurul Farhana; Neela, Vasantha Kumari; Hui, Yee Chee; Masri, Siti Norbaya; Mohamad Ikbal, Nurul Huda; Bhassu, Subha; Omar, Hasmahzaiti; M. Jamil Al-Obaidi, Mazen; Mohd Desa, Mohd Nasir (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Limited studies have been documented on the presence of pathogenic Leptospira in public markets serving the community in sub-districts of Selangor. The aim of this study was to detect the presence of pathogenic Leptospira in rats using a gene encoding an outer membrane lipoprotein LipL32. Methods: Polymerase chain reaction (PCR) was performed using LipL32 primers on sixty kidney samples of rats trapped at two locations of study; Pasar Borong Selangor in Seri Kembangan and Pasar Basah Bandar Baru Bangi in Bangi. Results: Out of 60 samples analysed, 36.7% were positive for the presence of LipL32. All positive samples highly matched (>94%) nucleotide sequence for LipL32 of pathogenic Leptospira and related to the pathogens through phylogenetic analysis. Conclusion: The detection of LipL32 indicates the potential presence of pathogenic Leptospira species at public markets. Although only 60 rats were successfully trapped, the rats are mobile and might further transmit the pathogenic organisms to other areas.